Al-Mahżūrāt al-Lughawiyyah fi Waśāil al-Tawāśul al-Ijtimā’ī wa Aśruhā al-Salbī ala Fasād Akhlāq al-Syabāb fi al-‘Ālam al-Islāmī (Linguistic Taboos in Social Media and Their Negative Impact on Deterioration of Morals of the Youth in the Islamic World) - Ibrahima Aliyu Yunus; Muhammad Isnan Sulaiman (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2022)
تدور فكرة هذا المقال المعنون بــــ